Life cycle assessment of PV module repowering. (September 2022) - Herceg, Sina; Fischer, Marie; Weiß, Karl-Anders; Schebek, Liselotte
Abstract: To mitigate the effects of climate change, the massive deployment of renewable energies is a key challenge in the near future. While for wind power plants, repowering is common practice to increase the energy yield, the early replacement of old photovoltaic (PV) modules with newer, more efficient ones is receiving less attention in industry, politics and research. In recent years, significant technological improvements have led to a reduction of energy and material use in the production as well as to an increase in PV system efficiencies. To assess the ecological implications of PV repowering, a life cycle assessment has been performed for a 3 kWp rooftop silicon PV plant and for a 1.07 MWp open field silicon PV plant for the two reference-production years of 2004 and 2020. The earliest and the optimum points in time, at which a premature replacement can be ecologically beneficial have been calculated for the indicators Climate change, Ecotoxicity, freshwater, Land use and Resource use, minerals and metals . Three scenarios, that differ regarding the respective repowering goal and the end-of-life treatment, have been analyzed. The calculated optimum repowering time for the investigated PV plants lies between 15 and 21 years on average, while it varies significantly between scenarios as well as impact indicators. The results show that a dedicated recycling as well as a repowering above the initial peak power are crucial in making repowering a sustainable option. Moreover, our calculation approach can be used to assess further technological variations at different reference years by using life cycle impact assessment results. It must be noted, these results are based on the technological progress achieved between 2004 and 2020. As it cannot be assumed that the technological progress of the last two decades can be projected into the future to the same extent, assumptions will have to be adapted for calculations for future time periods. Highlights: Optimum environmental repowering time for PV plants is between 15 and 21 years. Dedicated recycling is crucial for sustainable repowering. Lowest environmental impacts when the entire available area is used for repowering. a new calculation approach for optimum PV repowering is presented.